Nilai-Nilai Pendidikan Nasionalis Religius dalam Buku Negeri Daging: Kumpulan Puisi Karya KH. A. Mustofa Bisri - Choirul Mahmudi; Rohmat Dwi Yunianta (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
Book of Negeri Daging: Kumpulan Puisi (The Land of Meat: A Collection of Poetry) by KH. A. Mustofa Bisri was a collection of poetry that presented religious nationalist values. This book had educational values that could serve as a guide in the formation of the religious-nationalist character of society in the current era. This study was a type of qualitative research, which emphasized the use of theory from an analytical-descriptive way of thinking. Collecting data in this study was using data collection methods related to research, such as books, journals related to research, and others. Data analysis in this study used literary content analysis techniques, because the object studied was poetry which was part of a literary work. Research Results on educational values of religious nationalism in Book of Negeri Daging: Kumpulan Puisi by KH. A. Mustofa Bisri succeeded in explaining several points, namely: (a) grouping poetry which had values of maintaining honor, maintaining unity, mutual help, tolerance, independence, good character, values of justice and equal treatment, fulfilling promises, compassion and preventing damage. (b) a more detailed explanation of the relevance of the educational values of religious nationalism in book of Negeri Daging: Kumpulan Puisi by KH. A. Mustofa Bisri on material, media, and current educational goals, especially in Islamic education.